Bioplastics: a better option for the environment? - Maia Patterson McGuire (EDIS)
Most modern-day plastics are made from petroleum, but several different types of plastics are made from plant or even bacterial sources. This 4-page fact sheet written by Maia Patterson McGuire and published by the UF/IFAS School of Forest Resources and Conservation describes four types of these bioplastics and explains why, even if a bioplastic item is listed as “compostable,” a reusable, washable alternative is often the better choice. http://edis.ifas.ufl.edu/fr418